THE RELATIONSHIP BETWEEN SATISFACTION AND DONOR ROUTINES IN DONATING BLOOD AT UDD PMI SUMEDANG WEST JAVA: - Dea Putri Amalia; Iyos Sutresna; Heri Ridwan (Buletin Veteriner Udayana, 2024)
Good service in blood donation services is provided by officers who are declared competent. This aims to ensure that blood donors are willing to become voluntary blood donors who regularly donate blood, so that blood needs are met. The purpose of this research is to determine donor satisfaction during blood donation, to find out blood donation routines and to determine the relationship between satisfaction with blood donation routines. This research is a type of correlation research, namely determining whether there is a relationship between blood donor satisfaction and blood donation routine. This research sample used the accidental sampling technique method with a sample size of 95 respondents and data analysis used a computer program SPSS with bivariate and univariate analysis. After conducting the research, it was found that the characteristics of blood donors based on gender were more than half of the respondents, 53 people (56.4%), based on age, more than half of the respondents were 18-24 years old, 69 people (73.4%) , more than half of the respondents were students with a total of 68 people (72.3%). The results of research on the relationship between satisfaction and donor routine in carrying out blood donations at UDD PMI Sumedang in 2024 showed that the majority, namely 86 respondents (91.5%) felt very satisfied and the majority, namely 80 respondents (85.1), routinely carried out donor activities. blood. So the percentage relationship between satisfaction with blood donors and blood donation routines is obtained with a value of ρ = 0.00, meaning that Ho is rejected, thus there is a relationship between satisfaction with blood donors and blood donation routines. The value of the correlation strength level is 0.01, it can be said that the relationship is very weak and this relationship has a positive value, which means that the higher the satisfaction, the higher the blood donation routine is carried out. Therefore, it is very important that blood donation services further develop their quality to improve blood donation routines.